Bone Marrow Concentrate in the Treatment of Aneurysmal Bone Cysts: A Case Series Study - Lorenzo Andreani; Sheila Shytaj; Elisabetta Neri; Fabio Cosseddu; Antonio D’Arienzo; Rodolfo Capanna (Stem Cells International)
Introduction. A recent attractive option regarding mesenchymal stem cells (MSC) application is the treatment of bone cystic lesions and in particular aneurysmal bone cysts (ABC), in order to stimulate intrinsic healing. We performed a retrospective evaluation of the results obtained at our institution. Methods. The study group consisted of 46 cases with an average follow-up of 33 months. Forty-two patients underwent percutaneous treatment as the first approach; four patients had curettage as first treatment. In all cases, autologous bone marrow concentrate (BMC) was associated too. The healing status was followed up through a plain radiograph 45 days and 2 months after the procedure. Results and Conclusions. At the final follow-up, thirty-six patients healed with a Neer type II aspect, nine healed with a type I aspect, and one patient was not classified having total hip arthroplasty. Bone marrow concentrate is easy to obtain and to manipulate and can be immediately available in a clinical setting. We can assert that the use of BMC must be encouraged being harmless and having an unquestionable high osteogenic and healing potential in bone defects.